Perceptions of the Impact Of Availability and Utilisation of Laboratory Facilities On Science Teacher-Trainees’ Knowledge and Attitudes Toward Improvisation In Science - Nelson Mandela Anane; Vincent Ankamah Lomotey (Research Synergy Foundation, 2023)
The study examined final-year science teacher-trainees’ perceptions of the impact of availability and utilization of laboratory facilities on their knowledge and attitudes towards improvisation of instructional materials in science at Accra and Ada Colleges of Education within the Greater Accra Metropolis in the Greater Accra Region of Ghana. The study resulted from personal observation of the majority of in-service Junior High School (JHS) science teachers' inability to effectively teach science to make it more comprehensible to students. The study adopted the quantitative approach with a descriptive cross-sectional survey design involving 62 teacher-trainees, 15 science tutors, and two college principals who were selected through a purposive sampling technique to participate. The main research instrument was the questionnaire. Reliability coefficients of 0.84 and 0.86 were established for tutors' and teacher-trainees questionnaires respectively, which indicated that the questionnaires were reliable. The primary data were analyzed using descriptive and inferential statistics. The analysis revealed that the science teacher-trainees at the Ada College of Education held the view that availability and utilization of science laboratory facilities have had a high and positive impact on their knowledge and attitudes towards improvisation of instructional materials in science; whereas, at the Accra College of Education, the science teacher-trainees opined that availability and utilization of science laboratory facilities have had a moderate and neutral impact on their knowledge and attitudes towards improvisation of science instructional materials. It was recommended that the Ministry of Education provide adequate science laboratory facilities to promote the study of science and improve science teacher-trainees knowledge and attitudes towards improvisation in science, especially at the Accra College of Education.